2018
DOI: 10.1021/acs.jmedchem.8b01256
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of Clinical Candidate 2-(4-(2-((1H-Benzo[d]imidazol-2-yl)thio)ethyl)piperazin-1-yl)-N-(6-methyl-2,4-bis(methylthio)pyridin-3-yl)acetamide Hydrochloride [K-604], an Aqueous-Soluble Acyl-CoA:Cholesterol O-Acyltransferase-1 Inhibitor

Abstract: [2][3][4]imidazol-2-yl)thio)ethyl)piperazin-1-yl)-N-(6-methyl-2,4-bis(methylthio)pyridin-3-yl)acetamide hydrochloride (K-604, 2) has been identified as an aqueous-soluble potent inhibitor of human acyl-coenzyme A:cholesterol O-acyltransferase (ACAT, also known as SOAT)-1 that exhibits 229-fold selectivity for human ACAT-1 over human ACAT-2. In our molecular design, the insertion of a piperazine unit in place of a 6methylene chain in the linker between the head (pyridylacetamide) and tail (benzimidazole) moieti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 56 publications
(94 reference statements)
0
13
0
Order By: Relevance
“…Although an extremely high aqueous solubility (19 mg/mL) of K-604 has been reported at pH 1.2, this solution formulation is very invasive to nasal epithelial tissues because of its corrosive acidity. When using a 0.01 N HCl solution, the acidity was somewhat weakened to 2.3, but the solubility decreased to 3.24 mg/mL.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Although an extremely high aqueous solubility (19 mg/mL) of K-604 has been reported at pH 1.2, this solution formulation is very invasive to nasal epithelial tissues because of its corrosive acidity. When using a 0.01 N HCl solution, the acidity was somewhat weakened to 2.3, but the solubility decreased to 3.24 mg/mL.…”
Section: Resultsmentioning
confidence: 99%
“…K-604 was developed for the treatment of acute coronary syndrome in this Phase II study by Kowa Company Ltd. (Tokyo, Japan) according to a previously reported method. 17 For use as an internal standard for the low-level quantification of K-604 in plasma and brain tissues, a highly deuterium-labeled compound, 2-(4-(2-((1 H -benzo[ d ]imidazol-2-yl-4,5,6,7- d 4 )thio)ethyl)piperazin-1-yl)- N -(6-methyl-2,4-bis(methylthio)pyridin-3-yl)acetamide was also prepared by Kowa Company Ltd. Hyaluronic acid (HA), citric acid (CA), and d -gluconic acid (GA) were purchased from Tokyo Chemical Industry Co., Ltd. (Tokyo, Japan). Sodium 2-(6-oxido-3-oxo-3,10-dihydroanthracen-9-yl)benzoate (uranine) and 5 H -dibenzo[ b , f ]azepine-5-carboxamide (carbamazepine) were purchased from FUJIFILM Wako Pure Chemicals Corporation (Osaka, Japan).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Benzimidazoles have various of biological activities, such as anti-bacterial, anti-inflammatory, anti-tumor, and so on [11][12][13][14][15]. Studies have shown that the benzimidazole scaffold rings play a critical role in the antitumor activity [16,17].…”
Section: Introductionmentioning
confidence: 99%